(untitled) (Journal of Naval Architecture and Marine Engineering, 2012)
The sloshing phenomenon of liquid in a partially filled tank mounted rigidly on a barge exposed to random beam waves has been investigated through a well controlled experimental program. Four relative liquid depths, (liquid depth, hs/ length of tank, l) of 0.163, 0.325, 0.488 and 0.585 were considered for the tests. The sloshing oscillation was measured along the length of the tank at predefined locations. The effect of variation of the peak wave excitation frequency on the sloshing oscillation in the frequency domain is studied. The dominant energy is found to be concentrated around lowest nth sloshing mode frequency and, secondary peaks are observed at higher order sloshing frequencies. Odd modes contributions are dominating even modes irrespective of the excitation peak frequency. The sacrifice of second mode is observed while the excitation peak frequency is closer to its primary resonance. DOI: http://dx.doi.org/10.3329/jname.v9i1.7600 Journal of Naval Architecture and Marine Engineering 9(2012) 43-65